Validated HPLC Method For Determination Of Repaglinide In Human Plasma Using Liquid-Liquid Extraction. - Abu Bakar, Ruzilawati; Abd. Wahab, Mohd Suhaimi; lmran, Ahmad; Ismail, Zabidah; Siew, Hua Gan (2006)
Repaglinide is a novel prandial glucose regulator for the treatment of type 2 diabetes mellitus (Natrass, 2000; Hatorp et. at., 2003).